2002
DOI: 10.1002/jbm.a.10415
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen production by osteoblast‐like cells cultured in contact with different bioactive glasses

Abstract: Bioactive glasses are silica-based, surface-active bone substitutes that have shown good biocompatibility both in bone and in soft tissue and are used in oral and maxillofacial bone augmentation. Previous in vitro studies showing that bioactive glasses support the growth and maturation of rat osteoblast-like cells and promote the expression and maintenance of the osteoblastic phenotype have suggested that there is both a solution-mediated and a surface-controlled effect on cell activity. In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 27 publications
5
58
1
Order By: Relevance
“…Yao et al [46] noted that the dissolution products from poly(lactic-co-glycolic)/bioactive glass composite scaffold stimulated osteogenesis of rat marrow stromal cells, as was confirmed by increased mRNA expression of osteoblastic markers such as osteocalcin, alkaline phosphatase and bone sialoprotein. In another work [47], human primary osteoblast-like cells cultured in contact with melt-derived 45S5, as well as gel-derived 58S and 77S bioactive glasses revealed different behaviour, including ALP activity, as well as collagen type I expression and synthesis. The authors pointed out that the 45S5 glass significantly increased collagen secretion and ALP activity, compared to the other two gel-derived bioactive glasses, which can be related to alkalization of the culture medium.…”
Section: In Vitro Osteoblast Responsementioning
confidence: 95%
“…Yao et al [46] noted that the dissolution products from poly(lactic-co-glycolic)/bioactive glass composite scaffold stimulated osteogenesis of rat marrow stromal cells, as was confirmed by increased mRNA expression of osteoblastic markers such as osteocalcin, alkaline phosphatase and bone sialoprotein. In another work [47], human primary osteoblast-like cells cultured in contact with melt-derived 45S5, as well as gel-derived 58S and 77S bioactive glasses revealed different behaviour, including ALP activity, as well as collagen type I expression and synthesis. The authors pointed out that the 45S5 glass significantly increased collagen secretion and ALP activity, compared to the other two gel-derived bioactive glasses, which can be related to alkalization of the culture medium.…”
Section: In Vitro Osteoblast Responsementioning
confidence: 95%
“…Indeed, numerous in vivo and in vitro studies have shown that 45S5 Bioglass ® can stimulate bone regeneration (Bosetti et al 2003;Gough et al 2004;Livingston et al 2002;Loty et al 2001;Tsigkou et al 2007;Xynos et al 2000). As a result, Bioglass ® is said to be both osteoproductive and osteoconductive.…”
Section: Introductionmentioning
confidence: 99%
“…BG 13-93 is biodegradable, and when placed in an aqueous environment at 37°C, it converts to a calcium phosphate material analogous to hydroxyapatite [20,26]. As BG degrades, it also releases its ion content, which has the ability to stimulate osteoblast activity [3,4,40,42]. Previous studies have shown, in an osteoblast cell line, increasing the pH can improve collagen Type I production by increasing cellular metabolism [10,42].…”
Section: Discussionmentioning
confidence: 99%
“…Our work with an alternative silicate-based glass composition, Bioactive Glass 13-93 (BG 13-93), shows this composition can be readily shaped into porous constructs of complex shapes, while retaining the desirable in vitro bioactive characteristics of 45S5 glass and higher mechanical strength [16,32]. It is known, as BG degrades, it also releases its ion content, which has the ability to stimulate osteoblast activity [3,4,40,42]. However, there is currently a lack of studies investigating the effect of BG 13-93 on chondrocyte behavior and its use in cartilage tissue engineering.…”
Section: Introductionmentioning
confidence: 99%